Math Problem Statement

Die Fibonacci Zahlen fn f¨ur n ∈ N sind rekursiv definiert als f1 := 1, f2 := 1, fn := fn−1 + fn−2 f¨ur n ≥ 3. Zeigen Sie per Induktion: (a) Es gilt fn+m = fn−1fm + fnfm+1 f¨ur alle m ∈ N und n ≥ 2. Insbesondere folgt f2n = fn(fn−1 + fn+1) = f 2 n+1 − f 2 n−1 f¨ur alle n ≥ 2

Solution

To prove the given statement by induction, let’s tackle it in two parts. First, we’ll show that fn+m=fn1fm+fnfm+1f_{n+m} = f_{n-1} f_m + f_n f_{m+1} for all mNm \in \mathbb{N} and n2n \geq 2. Then we’ll demonstrate that this implies the specific relation f2n=fn(fn1+fn+1)=fn+12fn12f_{2n} = f_n (f_{n-1} + f_{n+1}) = f_{n+1}^2 - f_{n-1}^2 for all n2n \geq 2.

Part (a): Inductive Proof of fn+m=fn1fm+fnfm+1f_{n+m} = f_{n-1} f_m + f_n f_{m+1}

  1. Base Case: Let's prove the base case where m=1m = 1.

    • We need to show that fn+1=fn1f1+fnf2f_{n+1} = f_{n-1} f_1 + f_n f_2.
    • Since f1=f2=1f_1 = f_2 = 1, we have: fn1f1+fnf2=fn11+fn1=fn1+fn.f_{n-1} f_1 + f_n f_2 = f_{n-1} \cdot 1 + f_n \cdot 1 = f_{n-1} + f_n.
    • By the Fibonacci definition, fn+1=fn1+fnf_{n+1} = f_{n-1} + f_n, so the base case holds.
  2. Inductive Hypothesis: Assume that for some mNm \in \mathbb{N}, the formula holds: fn+m=fn1fm+fnfm+1.f_{n+m} = f_{n-1} f_m + f_n f_{m+1}.

  3. Inductive Step: We need to prove the statement for m+1m + 1: fn+(m+1)=fn1fm+1+fnfm+2.f_{n + (m + 1)} = f_{n-1} f_{m+1} + f_n f_{m+2}. Using the Fibonacci recurrence relation, we know: fn+(m+1)=fn+m+1=fn+m+fn+m1.f_{n + (m+1)} = f_{n+m+1} = f_{n+m} + f_{n+m-1}. By the inductive hypothesis, we can substitute fn+mf_{n+m} and fn+m1f_{n+m-1}: fn+m=fn1fm+fnfm+1,f_{n+m} = f_{n-1} f_m + f_n f_{m+1}, fn+m1=fn1fm1+fnfm.f_{n+m-1} = f_{n-1} f_{m-1} + f_n f_m. Therefore, fn+m+1=(fn1fm+fnfm+1)+(fn1fm1+fnfm).f_{n+m+1} = (f_{n-1} f_m + f_n f_{m+1}) + (f_{n-1} f_{m-1} + f_n f_m). Rearranging terms, we have: fn+m+1=fn1(fm+fm1)+fn(fm+1+fm).f_{n+m+1} = f_{n-1} (f_m + f_{m-1}) + f_n (f_{m+1} + f_m). Using the Fibonacci property fm+1=fm+fm1f_{m+1} = f_m + f_{m-1} and fm+2=fm+1+fmf_{m+2} = f_{m+1} + f_m, we find: fn+m+1=fn1fm+1+fnfm+2.f_{n+m+1} = f_{n-1} f_{m+1} + f_n f_{m+2}. This completes the inductive step, so by induction, the formula holds for all mNm \in \mathbb{N} and n2n \geq 2.

Part (b): Proving f2n=fn(fn1+fn+1)=fn+12fn12f_{2n} = f_n (f_{n-1} + f_{n+1}) = f_{n+1}^2 - f_{n-1}^2

Using the result from Part (a) for m=nm = n, we have: f2n=fn1fn+fnfn+1=fn(fn1+fn+1).f_{2n} = f_{n-1} f_n + f_n f_{n+1} = f_n (f_{n-1} + f_{n+1}).

To show the equivalence with f2n=fn+12fn12f_{2n} = f_{n+1}^2 - f_{n-1}^2:

  1. Start with the identity: fn+12fn12=(fn+1fn1)(fn+1+fn1).f_{n+1}^2 - f_{n-1}^2 = (f_{n+1} - f_{n-1})(f_{n+1} + f_{n-1}).
  2. Using the Fibonacci recurrence, we know fn+1fn1=fnf_{n+1} - f_{n-1} = f_n. Substitute this into the expression: fn+12fn12=fn(fn+1+fn1).f_{n+1}^2 - f_{n-1}^2 = f_n (f_{n+1} + f_{n-1}). Thus, we have shown: f2n=fn(fn1+fn+1)=fn+12fn12,f_{2n} = f_n (f_{n-1} + f_{n+1}) = f_{n+1}^2 - f_{n-1}^2, which completes the proof.

Summary

This concludes the inductive proof of both parts. Let me know if you need more details or clarification on any step!


Related Questions:

  1. What is the next step if we want to generalize this formula further?
  2. How can we use matrix representations to prove properties of Fibonacci numbers?
  3. Can we extend this formula to other sequences defined by a similar recurrence relation?
  4. How does this identity help in computational applications involving Fibonacci numbers?
  5. Can you find a similar identity for the Lucas sequence?

Tip:

For complex Fibonacci proofs, breaking down the recurrence into smaller cases often simplifies the process.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Induction
Fibonacci Sequence
Recursive Sequences

Formulas

f_n = f_{n-1} + f_{n-2} for n ≥ 3
f_{n+m} = f_{n-1} f_m + f_n f_{m+1}
f_{2n} = f_n (f_{n-1} + f_{n+1}) = f_{n+1}^2 - f_{n-1}^2

Theorems

Mathematical Induction

Suitable Grade Level

Grades 11-12